Effectiveness and early postoperative outcomes of palliative endoluminal stenting versus Hartmann’s procedure in acute malignant bowel obstruction in high-risk patients - Mohammed Fayek Mahfouz; Tamer M. Saeid Salama; Amr H. Afifi; Hany Mansour Khalil Dabous (Annals of Coloproctology, 2022)
Purpose The emergency intervention for acute malignant left-sided colonic obstruction remains controversial. Conflicting reports exist regarding the efficacy and safety of endoscopic placement of self-expandable metallic stents (SEMS) vs. primary surgery. Most reports focus on SEMS insertion as a bridge to surgery. Methods An observational nonrandomized study at a single center in Cairo, Egypt included 65 high-risk patients (American Society of Anesthesiologists physical status classification ≥ III, age > 60 years) with acute malignant metastatic (stage IV) colonic obstruction. Twenty-nine patients underwent primary surgery (Hartmann’s procedure, HP), and 35 patients underwent SEMS insertion. Results All cases that underwent SEMS insertion were technically successful. The 2 procedures were comparable in clinical success rates but a statistically significant difference existed between them regarding the duration of postoperative hospital stay in the HP and SEMS group (7.7 ± 3.1 days vs. 3.5 ± 0.6 days, retrospectively; P < 0.001), the interval before regaining oral feeding (41.8 ± 26.8 hours vs. 27.6 ± 18.5 hours, retrospectively; P = 0.015), and the duration of intensive care unit (ICU) admission (5.0 ± 1.7 days vs. 1.5 ± 0.7 days, retrospectively; P = 0.035). Six patients (20.7%) in the HP group and 2 patients (5.7%) in the SEMS group required postoperative ICU admission. Conclusion SEMS placement provides comparable efficacy and safety to HP in managing acute malignant obstruction of the rectosigmoid region in high-risk individuals, with faster recovery and less hospital and ICU admission time.